Al-Nakirah wa al-Ma'rifah fi Surati al-Naba'/النكرة والمعرفة في سورة النبأ - Yusuf, Eka Sandri; Pakaya, Nurul 'Aini; Saleh, Sriwahyuningsih R.; P. Doni, Chaterina (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Surah An-Naba' in the Holy Qur'an is one of the chapters rich in message and meaning. This surah employs both nakirah (indefinite) and ma'rifah (definite) nouns, which play a crucial role in conveying the message and enriching the structure of the Arabic language. To date, studies specifically addressing the types of nakirah and ma'rifah nouns and their grammatical analysis in Surah An-Naba' are limited. Therefore, this research aims to provide an understanding of the "Types of Nakirah and Ma'rifah Nouns and Their Grammatical Analysis in Surah An-Naba'." The objectives of this study are: (1) To identify the types of nakirah nouns and analyze their grammatical roles in Surah An-Naba'. (2) To identify the types of ma'rifah nouns and analyze their grammatical roles in Surah An-Naba'. The research methodology employed by the author in this study is qualitative descriptive research. The method used for data collection is the library research method. The sources of the materials investigated in this study are divided into two types: primary sources and secondary sources. The findings of the research include several key points obtained through the author's procedures, such as: (1) The number of nakirah nouns in Surah An-Naba' is found in thirty-four (34) verses. (2) The number of ma'rifah nouns in Surah An-Naba' is found in thirty-two (32) verses. It can be concluded that the study of nakirah and ma'rifah nouns is essential for understanding the Qur'an. The purpose of this learning is to prevent errors in the interpretation of the Qur'an, the Hadith of the Prophet, and other texts.